A misexpression study examining dorsal thorax formation in Drosophila melanogaster. - Peña-Rangel, María Teresa (2002)
We studied thorax formation in Drosophila melanogaster using a misexpression screen with EP lines and thoracic Gal4 drivers that provide a genetically sensitized background. We identified 191 interacting lines showing alterations of thoracic bristles (number and/or location), thorax and scutellum malformations, lethality, or suppression of the thoracic phenotype used in the screen. We analyzed these lines and showed that known genes with different functional roles (selector, prepattern, proneural, cell cycle regulation, lineage restriction, signaling pathways, transcriptional control, and chromatin organization) are among the modifier lines. A few lines have previously been identified in thorax formation, but others, such as chromatin-remodeling complex genes, are novel. However, most of the interacting loci are uncharacterized, providing a wealth of new genetic data. We also describe one such novel line, poco pelo (ppo), where both misexpression and loss-of-function phenotypes are similar: loss of bristles and scutellum malformation.